Authenticity and the Cyber Pilgrim - Xiarhos, Michael (The journal of religion & society, 2016)
Pilgrimage is a spiritual-physical act done by adherents of every major faith system. Complicating the traditional pilgrimage ethos is the so-called virtual pilgrimage: a concept that I argue is not a product of modernity nor an act of the spiritually unmotivated, but rather something that was conceptually born in the fifteenth century as a response to feelings of ultimate devotion. The works of Felix Fabri illustrate how a potential pilgrim may "be out there" without ever stepping foot on an actual pilgrim road. This practice is becoming more commonplace due to advancements in the Internet and virtual reality. Thus humanity may have reached a point at which online pilgrimage or online faith worship could challenge more traditional formations of faith and practice.